Syphilis and parvovirus B19 co-infection imitating a lupus nephropathy: A case report. Issue 36 (September 2019) - Jaunin, Eric; Kissling, Sebastien; Rotman, Samuel; Waeber, Gérard; Halfon, Matthieu
Abstract: Rationale: Syphilis can share clinical features with autoimmune diseases, such as cutaneous Lupus or rheumatoid arthritis. Moreover, secondary syphilis can have visceral involvement, thus affecting the kidney. Syphilitic nephropathy causes nephrotic syndrome with a classic membranous pattern. We present a unique presentation of a co-infection by syphilis and parvovirus B19 sharing all the biological and histological features of proliferative lupus nephritis (LN). Patient concerns: We present a case of a 71-year-old Caucasian male returning from a trip to Asia presenting with nephrotic syndrome with antinuclear antibodies (ANA) positivity. Diagnoses: Because of nephrotic syndrome a kidney biopsy was performed. It demonstrated a membranous nephropathy with extracapillary proliferation and a full house pattern (presence of IgA, IgG, IgM and C1Q deposits) on immunofluorescence (IF), highly suggestive of LN class III and V. However, several atypical clinical features notably the age, sex of the patient and the history of travel prompt us to search for another cause of nephropathy. Interventions: A serology was positive for syphilis and a PCR in the renal biopsy was also positive for parvovirus B19. Thus, a co-infection by syphilis and parvovirus B19 was funded to be the cause of the renal lesions. Outcomes: The proteinuria improved; a course of antibiotic was administrated because of neurologic syphilitic involvement (presence of headache with positive syphilis serology in the CSF). Lessons: A co-infection by syphilis and parvovirus B19 can share all the biological and histological features of proliferative LN and must be recognized as a cause of pseudo-lupus nephritis.